Penggunaan Metode Inquiry untuk Meningkatkan Motivasi Belajar Pendidikan Agama Islam Kelas XI SMK Negri 1 Donggo Kecematan Donggo Kabupaten Bima - Ratih Puspitasari; Syafruddin Syafruddin; Irwan Irwan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to address the low learning motivation of students in Islamic Religious Education (PAI) at SMK Negeri 1 Donggo. The primary issue identified is the dominance of conventional teaching methods, which result in student passivity and boredom. This research explores how the implementation of the Inquiry method can serve as a solution to foster active engagement and students' desire to understand religious values independently and critically. This research employs a Classroom Action Research (CAR) design following the Kemmis & McTaggart model, conducted in two cycles. Each cycle consists of planning, acting, observing, and reflecting stages. The research subjects comprised 24 eleventh-grade students at SMK Negeri 1 Donggo. Data were collected using validated instruments, including student activity observation sheets and learning motivation questionnaires. Data analysis was performed using descriptive quantitative techniques to measure the percentage increase in learning motivation from the pre-cycle condition to the final cycle. The research findings demonstrate a significant and gradual increase in learning motivation. In the pre-cycle stage, the average student learning motivation was only 43.25% (low category). Following the implementation of the Inquiry method in Cycle I, this figure rose to 61.25% (moderate category). The peak was reached in Cycle II, where through improved investigative guidance, student learning motivation reached 83.75% (high category). These results confirm that the Inquiry method is effective in shifting the student learning paradigm from passive listeners to active discoverers of knowledge. This study is limited to a single class at SMK Negeri 1 Donggo, focusing specifically on the learning motivation variable. Practical implications of this study suggest that PAI educators should integrate contextual inquiry steps to enhance the quality of classroom interaction. Theoretically, this research reinforces the relevance of constructivism theory in religious education at the vocational high school level